X-linked lymphoproliferative disease with initial onset of neurological symptoms: a case and literature review - Zhang, Lijun; Li, Deyuan; Wang, Jianjun; Zhang, Haiyang; Chen, Jun; Liu, Zhongqiang (Frontiers in Immunology, 2025)
X-linked lymphoproliferative syndrome type 1 (XLP-1) is a life-threatening X-linked recessive immunodeficiency classically characterized by susceptibility to Epstein–Barr virus (EBV), hypogammaglobulinemia, and lymphoma. While neurological involvement can occur, it is exceptionally rare as the initial and predominant manifestation. This case report details a novel presentation of XLP-1 in a 4-year-old boy who presented with acute, initial neurological symptoms (sudden fever, headache, and vomiting) in the absence of typical immune dysregulation features. Whole-exome sequencing (WES) identified a hemizygous variant in the SH2D1A gene (c.1A>G, p. Met1Val), predicted as damaging/disease-causing by MutationTaster (probability = 0.993) and PolyPhen-2 (probability = 0.992). Meanwhile, according to the American College of Medical Genetics and Genomics (ACMG) guidelines for variant interpretation, this variant met four evidence criteria (PVS1_Moderate+ +PM2_Moderate+PP3+PP5) and was classified as pathogenic. Structural analysis leveraging the AlphaFold protein structure database demonstrated that this variant disrupts the Kozak consensus sequence and splice site, critically impairing start codon recognition and translation initiation, thereby explaining the loss of functional SLAM-associated protein (SAP) protein expression. This case, along with a focused review of the literature, underscores that XLP-1 rarely presents primarily with neurological symptoms, broadening the clinical phenotype spectrum and emphasizing the need for early genetic evaluation in children with unexplained acute neurological presentations, even in the absence of overt immunodeficiency signs. This finding provides crucial clinical data for a more comprehensive understanding of XLP-1.